Immediate versus delayed implant placement in the esthetic zone: a prospective 3D volumetric assessment of peri-implant tissue stability - Puria Parvini; Katharina Melissa Müller; Emilio A. Cafferata; Frank Schwarz; Karina Obreja (International Journal of Implant Dentistry, 2022)
Abstract Purpose To evaluate the volumetric stability of peri-implant soft and hard tissue prospectively, this study compared immediate versus delayed implants placed in the anterior esthetic region. Methods This non-randomized controlled clinical study included 25 patients, who received an immediate (type 1) or a delayed (type 4) implant placement for the replacement of a single anterior tooth. The anterior maxillae were intraorally scanned at three timepoints: before surgery (S0), 6 months (S1), and 12 months (S2) after surgery. A specific region of interest (ROI), divided into marginal and apical regions, was determined and superimposed for volumetric changes analysis. At 6 and 12 months, the probing depth (PD), bleeding/suppuration on probing (BOP/SUP), modified plaque index (PI), keratinized mucosa (KM) width, mucosal recession (MR), and implant stability (PTV) by means of periotest were recorded. Results Between S0–S2, tissue surrounding immediate implants was reduced in 0.37 ± 0.31 mm, whereas delayed implants gained 0.84 ± 0.57 mm mean tissue volume. Peri-implant tissue loss at type 1 implants occurred primarily in the marginal section of the ROI (0.42 ± 0.31 mm), whereas tissue gain at type 4 implants occurred mainly in the apical section (0.83 ± 0.51 mm). These values were significantly different between both groups for the entire ROI (p = 0.0452) and the marginal region (p = 0.0274). In addition, the mean buccal KM width around type 1 implants was significantly wider in comparison with the type 4 implants group after 12 months (p = 0.046). There were no significant differences between groups regarding PD, BOP/SUP, or PTV. Conclusions The results suggest that type 1 implants placed in the esthetic region experience more tissue loss than type 4 implants, thus marginal tissue remodeling should be considered for planning immediate implants placement in the anterior maxillae. Graphical Abstract